Factors Associated With Shift Work Disorder in Nurses Working With Rapid-Rotation Schedules in Japan: The Nurses' Sleep Health Project. (May 2013) - Asaoka, Shoichi; Aritake, Sayaka; Komada, Yoko; Ozaki, Akiko; Odagiri, Yuko; Inoue, Shigeru; Shimomitsu, Teruichi; Inoue, Yuichi
<x xml:space="preserve">Abstract</x> Workers who meet the criteria for shift work disorder (SWD) have elevated levels of risk for various health and behavioral problems. However, the impact of having SWD on shiftworkers engaged in rapid-rotation schedules is unknown. Moreover, the risk factors for the occurrence of SWD remain unclear. To clarify these issues, we conducted a questionnaire-based, cross-sectional survey on a sample of shiftworking nurses. Responses were obtained from 1202 nurses working at university hospitals in Tokyo, Japan, including 727 two-shift workers and 315 three-shift workers. The questionnaire included items relevant to age, gender, family structure, work environment, health-related quality of life (QOL), diurnal type, depressive symptoms, and SWD. Participants who reported insomnia and/or excessive sleepiness for at least 1 mo that was subjectively relevant to their shiftwork schedules were categorized as having SWD. The prevalence of SWD in the sampled shiftworking nurses was 24.4%; shiftworking nurses with SWD showed lower health-related QOL and more severe depressive symptoms, with greater rates of both actual accidents/errors and near misses, than those without SWD. The results of logistic regression analyses showed that more time spent working at night, frequent missing of nap opportunities during night work, and having an eveningness-oriented chronotype were significantly associated with SWD. The present study indicated that SWD might be associated with reduced health-related QOL and decreased work performance in shiftworking nurses on rapid-rotation schedules. The results also suggested that missing napping opportunities during night work, long nighttime working hours, and the delay of circadian rhythms are associated with the occurrence of SWD among shiftworking nurses on rapid-rotation schedules. (Author correspondence: yuinoue@tokyo-med.ac.jp)